Online Monitoring for Multiple Devices Power Consumption - Ahmad, Aliuddin Asyraf; Hanafi, Dirman (Evolution in Electrical and Electronic Engineering, 2023)
The electrical meter has evolved over the years alongside technological advancements, beginning with the classic mechanical energy meter and progressing all the way up to the most recent technologies based on the Internet of Things (IoT). The advantages of this project are it will be able to assist consumers in monitoring the amount of power used by each of their electrical appliances and also the user is now able to monitor the power consumption of each electrical appliance using their smartphone (both iOS and Android versions are supported) or a computer running Windows OS thanks to the extra IOT system that has been integrated into this system. Consumers are also able to view the monthly utility bill that they get according to the tariff by TNB. Because this system is totally wireless, customers can monitor their home appliances from virtually any location, provided they have an internet connection. There are 3 parameters that need to be measured and compared which are voltage, current and real power using a clamp meter and a developed prototype to test the performance of this system prototype. The result of the test showed that the error that this developed prototype has in its reading of voltage for lamp 1 is 0.855%, the table fan is 0.426% and lamp 2 is 0.819%. After that, the error that it has in its reading of current for lamp 1 is 3.333%, the table fan is 2.083%, and lamp 2 is 1.613%. Lastly, the error that it has in its reading of real power for lamp 1 is 8.383%, the table fan is 12.848%, and lamp 2 is 2.953%. By providing users with this information, it will be possible to raise their awareness of the need to minimize the amount of energy they use and develop a strategy for energy savings.